Exploring the attributes of hotel service quality in Florianópolis-SC, Brazil: An analysis of tripAdvisor reviews - Clérito Kaveski Peres; Edson Pacheco Paladini (Cogent Business & Management, 2021)
This study explores user-generated content (UGC) of the hotel sector in the city of Florianópolis-SC, Brazil, to identify the quality attributes of services and determine the polarity of the expressed feelings in the reviews of each attribute. The analysis is based on the latent topics and the polarity of feelings expressed in the reviews. UGC was collected using a crawler, resulting in a text corpus comprising 68,558 reviews. The polarity of feelings, positive or negative, was identified using sentiment analysis techniques and Latent Dirichlet Allocation (LDA) was used to identify latent topics in the corpus associated with the attributes of hotel service quality. This study found that 'room,' 'location,' 'ambience,' 'staff,' 'breakfast,' 'parking,' 'reservation,' and 'cost-benefit' were the attributes most frequently assessed by consumers in their reviews. The attributes that generate the most negative reviews were 'room,' 'parking,' and 'reservation.' The attributes 'location,' 'ambience,' 'staff,' 'breakfast,' and 'cost-benefit' were the attributes that generated most of the positive reviews. When comparing the results of this study to those of previous studies, two attributes demonstrated greater prominence: the attribute 'room' that attracted a high number of negative comments and the attribute 'parking' that had not presented itself with the same level of relevance in other studies.
Keywords: 650; hospitality; Latent Dirichlet Allocation; sentiment analysis